Pengembangan Buku Cerita pada Materi Operasi Hitung Penjumlahan dan Pengurangan Bilangan Cacah Siswa Kelas II SD Negeri Gandok Yogyakarta - Inggrittina Bunga, Orolaleng; Trisniawati; Nelly, Rhosyida; Widodo, Sri Adi (LPPM Universitas Terbuka, 2024)
This study aims to develop storybooks on grade II mathematics material, describe the validity of the products resulting from the development of storybooks, and describe the practicality of the products produced. This research method is research and development (reseach and development). Researchers use R&D procedures according to ADDIE (Analyze, Design, Development, Implementation, and Evaluation). Data collection techniques were carried out through observation, interviews, and questionnaires. The subjects of this study were second grade students of Gandok State Elementary School. The data analysis technique used was data collection through questionnaires. The result of the research is a development product in the form of storybooks on mathematics learning materials for addition and subtraction of numerical numbers in grade II. On valid criteria, the results of the material expert validation obtained a percentage of 85%, while for the construction expert obtained a percentage of 97%. This the storybook developed is on very valid criteria. On practical criteria, both class teacher and learner responses get a percentage result of 100% or are on very practical criteria. From the responses of teachers and students, it can be stated that the storybooks developed get very practical criteria. Based on this, the storybook developed can be declared valid and practical. This storybook is expected to be an additional book in the process of learning grade II mathematics and increasing students' understanding of addition and subtraction counting operation.